Unleashing Twitter data for fun and insight - Russell, Matthew A. (Computer scientist) (O'Reilly Media, 2011)
"This talk demonstrates how an eclectic blend of storage, analysis, and visualization techniques can be used to gain a lot of serious insight from Twitter data, but also to answer fun questions such as "What does Justin Bieber and the Tea Party have (and not have) in common?"--Resource description page.